Understanding the Quality of Life and Its Related Factors in Orthodontics Postgraduate Students: A Mixed Methods Approach - Laura V. López-Trujillo; Sara C. López-Valencia; Andrés A. Agudelo-Suárez (MDPI AG, 2023)
This study analyzed the academic, sociodemographic, and labor conditions related to the quality of life (QOL) of orthodontics postgraduate students in Colombia. A mixed study (explanatory sequential design) was conducted. An online cross-sectional survey (n = 84; 64.3% females) was carried out with sociodemographic, academic, social support, health, labor, and QOL (WHOQOL-BREF) variables. Descriptive, bivariate analyses, and multivariate linear regression were performed. Focus groups (FGs) delved into aspects of relevance regarding QOL and determinants, through qualitative content analysis and triangulation of information. The median score in the four WHOQOL-BREF dimensions surpasses 50 points, with the highest score being in the psychological dimension (62.5 ± 16.7). According to the multivariate linear regression models, the variables significantly associated with QOL scores were playing sports, being married/living together, normal BMI, low social support, and medium/low socioeconomic status. The qualitative results explained the determinants of QOL in the personal, academic, and social dimensions of the participants. The discourses showed that the postgraduate course represents a resignification of their life, where their QOL is affected by the difficulties of their academic development, by the difficulty of reconciling the personal academic load with their affective, work, and social life, and by the stress they experience in their staff process. In conclusion, the participants' QOL was moderate and affected by different factors. The findings highlighted the importance of mental health promotion and well-being strategies in students of orthodontic postgraduate training programs in Colombia for improving QOL.